2021
DOI: 10.1108/mrr-08-2020-0517
|View full text |Cite
|
Sign up to set email alerts
|

The effect of auditor narcissism on audit market competition

Abstract: Purpose This paper aims to assess auditor narcissism’s effect on audit market competition (auditor concentration, clients’ concentration and competitive pressure). Design/methodology/approach This paper’s method is descriptive-correlational based on published information from listed firms on the Tehran Stock Exchange from 2012 to 2018 using a sample of 188 firms (1,310 observations). The method used for hypothesis testing is linear regression using panel data. Findings The results show a negative and signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
(73 reference statements)
2
10
0
Order By: Relevance
“…(2022) concluded that a positive and significant relationship exists between organizational justice and professional skepticism when organizational commitment is considered as a moderating variable. The significant effects of self-efficacy, self-esteem, spiritual intelligence and accountability pressures on auditors' efficiency (Salehi and Dastanpoor, 2021) and auditors' narcissism on auditors' market completion (Mohammadi et al ., 2021) have also been reported. While these studies are useful, they are not directly related to whistleblowing, which is the main focus of this study.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…(2022) concluded that a positive and significant relationship exists between organizational justice and professional skepticism when organizational commitment is considered as a moderating variable. The significant effects of self-efficacy, self-esteem, spiritual intelligence and accountability pressures on auditors' efficiency (Salehi and Dastanpoor, 2021) and auditors' narcissism on auditors' market completion (Mohammadi et al ., 2021) have also been reported. While these studies are useful, they are not directly related to whistleblowing, which is the main focus of this study.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This problem is especially important for large firms that rely on capital providers or lenders to operate. To obtain the necessary financing, such businesses must provide true financial information given by management and examined by specialized auditors (Alharasis et al, 2022c;Mohammadi et al, 2021). In the product differentiation scenario, auditors should charge high prices for their better services (fee premium).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to DeFond et al (2000) and Fung et al (2012), the first measure depicts the product differentiation scenario by capturing the audit firm's (ISP1) MS. This metric implies that auditors offer a superior and unique audit service to a certain sector, for which they charge a premium rate (Mohammadi et al, 2021). However, in accordance with Ettredge and Greenberg (1990) and Hay and Jeter (2011), the second metric is the PS of the industry (ISP2), which incorporates cost savings associated with efficiency improvements.…”
Section: Research Data and Sample Selection 41 Data Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Codes of corporate governance globally have gradually dispensed commendations for corporate board structures and, particularly, relating to its independent members (Crespí-Cladera & Pascual-Fuster, 2014; Mohammadi et al, 2021; Saeed et al, 2021a,b). Most regulators and academicians define a member independent if he or she has neither familial nor financial links to the firm or any other board member, and highpoint the monitoring profits of independent executives (e.g., Armstrong et al, 2014; Chen et al, 2015; Klein, 2002).…”
Section: Introductionmentioning
confidence: 99%